A Short History of Transport in Japan from Ancient Times to the Present. - Black, John Andrew (Cambridge, UK : Open Book Publishers, 2022)
A Short History of Transport in Japan from Ancient Times to the Present is a unique study: the first by a Western scholar to place the long-term development of Japanese infrastructure alongside an analysis of its evolving political economy. Drawing from New Institutional Economics, Black offers an historically informed critique of contemporary planning using the example of Japan's historical institutions, their particular biases, and the power they have exerted over national and local transport, to identify how reformed institutional arrangements might develop more sustainable and equitable transport services.
Intro -- Table of Contents -- Foreword -- 序文 -- Preface -- Acknowledgements -- 1. Introduction -- 2. Japanese Institutions and Organisations -- 3. Ports and Shipping -- 4. Canals, Rivers and Lakes -- 5. Roads -- 6. Railways -- 7. Civil Aviation and Airports -- 8. Urban Planning Institutions and the Integration of Land Use and Transport -- 9. Conclusions -- List of Figures -- List of Tables -- Index -- About the Cover -- About the Team.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Transportation--Japan--History.; Transportation--Economic aspects--Japan.; Transportation. (OCoLC)fst01155007.; Japan. (OCoLC)fst01204082.; History.0(OCoLC)fst01411628.; Electronic books